Kajian Teknis Produktivitas Alat Gali Muat Dan Alat Angkut Untuk Mencapai Target Produksipada Penambangan Andesit Di Pt. Balantak Sirtu Utama, Desa Batu Mandi, Kecamatan Balantak Utara, Kabupaten Banggai, Provinsi Sulawesi Tengah - Lestari, Widya; Partama Misdiyanta; Novandri Kusuma Wardana (Retii, 2023)
Balantak Sirtu Utama is a sirtu (stone sand) mining company located in Batu Mandi Village, North Balantak District, Banggai Regency, Central Sulawesi. PT. Balantak Sirtu Utama applies the open pit quarry system method with a planned production target of 52,908 m3/month. The mechanical device used by PT. Balantak Sirtu Utama is a Komatsu PC-300 excavator for the material loading process and a Fusso 220 PS 4x2 dump truck for material transportation. In the process of moving material from the location of the loading point to the dumping point, good management is needed so that production can be achieved, which of course will greatly affect the planned production. From the data obtained in the field, the cycle time of the Komatsu PC-300 excavator is not optimal because there is a lot of time wasted (delay) when loading activities are in progress, namely an average of 1.19 minutes. For the Fuso 220 PS dump truck cycle time, from the available data, it can also be explained that the cycle time of this conveyance is also not optimal because of the large number of waiting times for one transportation cycle when production activities take place, namely 8.25 minutes. If the loading pattern is changed from a single back-up loading pattern to a double back-up loading pattern, the production of the Komatsu PC-300 excavator loader can be increased to 99,719 m3/month, while the 220 PS Mitsubishi Fuso dump truck hauling equipment increases to 58,349 m3/month. And if front repairs are carried out with the distribution time of the loading and transport equipment having been optimized using the same number of equipment units, namely, 1 unit of Komatsu PC-300 excavator loading equipment and 4 units of Mitsubishi Fuso 220 PS dump truck conveyance, then the value will be obtained with a match factor of 1.62, which means that the loading equipment works 100% and the transportation equipment works less than 100% and there is still a waiting time for the transportation equipment. Keyword : Productivity, Cycle Time, Production, Match Factor